New Facies Model and Carbon Isotope Stratigraphy for an Ediacaran Carbonate Platform From South America (Tamengo Formation—Corumbá Group, SW Brazil) - Ramos, Maria E. A. F.; Giorgioni, Martino; Walde, Detlef H. G.; do Carmo, Dermeval A.; Fazio, Gabriella; Vieira, Lucieth C.; Denezine, Matheus; V. Santos, Roberto; R. Adôrno, Rodrigo; Lage Guida, Lucas (Frontiers in Earth Science, 2022)
The Ediacaran is a period characterized by the diversification of early animals and extensive neritic carbonate deposits. These deposits are still not well understood in terms of facies and carbon isotope composition (δ13C). In this study we focus on the Tamengo Formation, in southwestern Brazil, which constitutes one of the most continuous and well-preserved sedimentary record of the late Ediacaran in South America. We present new detailed lithofacies and stable isotopes data from two representative sections (Corcal and Laginha) and revise the paleoenvironmental and stratigraphic interpretation of the Tamengo Formation. The Corcal section consists of neritic deposits including shallow-water limestone beds, alternated with shale and subordinate marl beds. These facies yield specimens of the Ediacaran fossils Cloudina lucianoi and Corumbella werneri. On the other hand, the Laginha section shows more heterogeneous facies, such as impure carbonates, breccias, marls, and subordinate mudstone beds, as well as no evidence of Corumbella werneri. The stable carbon isotope record is also different between the two sections, despite belonging to the same unit. The Corcal section displays higher and more homogeneous δ13C values, consistent with those of Ediacaran successions worldwide. The Laginha section, instead, displays more variable δ13C values, which suggest the influence of local and post depositional processes. The difference between the two sections was attributed to the different distance from the shore. We propose that the difference is due to topographic variations of the continental platform, which, at the Laginha site, was steeper and controlled by extensional faults. Therefore, the Corcal section is a better reference for the Tamengo Formation, whereas the Laginha is more particular and influenced by local factors. Besides, the lithofacies associations of the Tamengo Formation are like those of the Doushantuo and Dengying formatios, in South China, with no significant biogenic carbonate buildups, and different from those of other important Ediacaran units, such as the Nama Group in Nmibia and the Buah Formation in Oman. Our work highlights the complexity and heterogeneity of Ediacaran carbonate platforms and of their carbon isotopic composition. In addition, we characterize the Corcal section as a possible reference for the Ediacaran in South America.